2016
DOI: 10.3390/ijms17060919
|View full text |Cite
|
Sign up to set email alerts
|

Potential Benefits of Dietary Fibre Intervention in Inflammatory Bowel Disease

Abstract: Intestinal dysbiosis is thought to be an important cause of disease progression and the gastrointestinal symptoms experienced in patients with inflammatory bowel disease (IBD). Inflammation appears to be a major contributor in perpetuating a dysregulated gut microbiota. Although current drug therapies can significantly induce and maintain disease remission, there is no cure for these diseases. Nevertheless, ongoing human studies investigating dietary fibre interventions may potentially prove to exert beneficia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 105 publications
2
60
0
2
Order By: Relevance
“…IBD is facilitated by immune hyper‐responsiveness towards certain intestinal microbiota, which is critical in stimulating mucosal immune disorders . Studies have shown that polysaccharides are capable of balancing the intestinal microbiota . We performed 16S rRNA gene sequencing on faecal samples from normal or acute colitis model mice treated with or without lentinan to investigate changes in intestinal microbiota because of lentinan treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IBD is facilitated by immune hyper‐responsiveness towards certain intestinal microbiota, which is critical in stimulating mucosal immune disorders . Studies have shown that polysaccharides are capable of balancing the intestinal microbiota . We performed 16S rRNA gene sequencing on faecal samples from normal or acute colitis model mice treated with or without lentinan to investigate changes in intestinal microbiota because of lentinan treatment.…”
Section: Resultsmentioning
confidence: 99%
“…34 Studies have shown that polysaccharides are capable of balancing the intestinal microbiota. 35,36 We performed Figure 7B). This finding is consistent with a previous study that reported a decrease of Firmicutes and an increase of Proteobacteria in IBD patients.…”
Section: Lentinan Restores the Intestinal Floral Structurementioning
confidence: 99%
“…49 As possible mode of actions, it is hypothesized that dietary fibers directly interact with the intestinal microbiome, eg, by modulating intestinal immune responses or by directly affecting intestinal microbiota composition. 20 Therefore, based on the literature, a fiber-rich diet seems to have beneficial effects for IBD patients and should be promoted by the treating physicians.…”
Section: Discussionmentioning
confidence: 99%
“…19 An important preventive measure in the management of IBD patients is to provide proper nutrition (especially a fiber-rich diet), that may play a role in maintaining remission in those patients. 20 The selection of a proper therapy, such as biological therapy, which is used with increasing frequency, seems not only to mitigate the inflammatory process in the gastrointestinal (GI) tract, but also to provide beneficial effects on the nutritional status of patients with CD, thus denoting the increasing importance of medications in vitamins and micronutrient levels. 21 Taken together current evidence suggests that vitamins might play an important role for the disease course and outcome of IBD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, fibers of different sources have varied effects on colitis, among which psyllium, pectin and cellulose fibers had protective effects contrary to methylcellulose . Additionally, the effect of dietary fiber varies between CD and UC …”
Section: Diet In the Pathogenesis Of Ibdmentioning
confidence: 99%